Using Information and Communication Technology in Italian Language Learning and Teaching: from Teacher Education to Classroom Activities - Matteo Viale (Caracteres: Estudios Culturales y Críticos de la Esfera Digital, 2017)
This paper describes the in-service teacher education activities carried out by the research unit from the University of Bologna involved in the European project E-LENGUA. This project focuses on the use of Information and Communication Technologies (ICTs) in teaching Italian in the multilingual classroom. The paper opens with a description of the Italian educational context, characterised by an increasing presence of non-native speakers of Italian. Taking into consideration the linguistic needs of students with different sociolinguistic backgrounds is a significant challenge for teachers. ICTs may be helpful for teachers facing such challenges, even though there are contrasting opinions about their usage in the classroom. The paper presents some case studies on the use of ICTs in the classroom, developed within in-service teacher education activities and implemented in the classroom. These studies aim to examine the use of ICTs as a teaching resource in order to elaborate generalizable guidelines for best practices in the Italian school system.